Paediatric Strategy Forum for medicinal product development of chimeric antigen receptor T-cells in children and adolescents with cancer: ACCELERATE in collaboration with the European Medicines Agency with participation of the Food and Drug Administration2. (January 2022) - Pearson, Andrew DJ.; Rossig, Claudia; Mackall, Crystal; Shah, Nirali N.; Baruchel, Andre; Reaman, Gregory; Ricafort, Rosanna; Heenen, Delphine; Bassan, Abraham; Berntgen, Michael; Bird, Nick; Bleickardt, Eric; et al.
Abstract: The seventh multi-stakeholder Paediatric Strategy Forum focused on chimeric antigen receptor (CAR) T-cells for children and adolescents with cancer. The development of CAR T-cells for patients with haematological malignancies, especially B-cell precursor acute lymphoblastic leukaemia (BCP-ALL), has been spectacular. However, currently, there are scientific, clinical and logistical challenges for use of CAR T-cells in BCP-ALL and other paediatric malignancies, particularly in acute myeloid leukaemia (AML), lymphomas and solid tumours. The aims of the Forum were to summarise the current landscape of CAR T-cell therapy development in paediatrics, too identify current challenges and future directions, with consideration of other immune effector modalities and ascertain the best strategies to accelerate their development and availability to children. Although the effect is of limited duration in about half of the patients, anti-CD19 CAR T-cells produce high response rates in relapsed/refractory BCP-ALL and this has highlighted previously unknown mechanisms of relapse. CAR T-cell treatment as first- or second-line therapy could also potentially benefit patients whose disease has high-risk features associated with relapse and failure of conventional therapies. Identifying patients with very early and early relapse in whom CAR T-cell therapy may replace haematopoietic stem cell transplantation and be definitive therapy versus those in whom it provides a more effective bridge to haematopoietic stem cell transplantation is a very high priority. Development of approaches to improve persistence, either by improving T cell fitness or using more humanised/fully humanised products and co-targeting of multiple antigens to prevent antigen escape, could potentially further optimise therapy. Many differences exist between paediatric B-cell non-Hodgkin lymphomas (B-NHL) and BCP-ALL. In view of the very small patient numbers with relapsed lymphoma, careful prioritisation is needed to evaluate CAR T-cells in children with Burkitt lymphoma, primary mediastinal B cell lymphoma and other NHL subtypes. Combination trials of alternative targets to CD19 (CD20 or CD22) should also be explored as a priority to improve efficacy in this population. Development of CD30 CAR T-cell immunotherapy strategies in patients with relapsed/refractory Hodgkin lymphoma will likely be most efficiently accomplished by joint paediatric and adult trials. CAR T-cell approaches are early in development for AML and T-ALL, given the unique challenges of successful immunotherapy actualisation in these diseases. At this time, CD33 and CD123 appear to be the most universal targets in AML and CD7 in T-ALL. The results of ongoing or planned first-in-human studies are required to facilitate further understanding. There are promising early results in solid tumours, particularly with GD2 targeting cell therapies in neuroblastoma and central nervous system gliomas that represent significant unmet clinical needs. Further understanding of biology is critical to success. The comparative benefits of autologous versus allogeneic CAR T-cells, T-cells engineered with T cell receptors T-cells engineered with T cell receptor fusion constructs, CAR Natural Killer (NK)-cell products, bispecific T-cell engager antibodies and antibody-drug conjugates require evaluation in paediatric malignancies. Early and proactive academia and multi-company engagement are mandatory to advance cellular immunotherapies in paediatric oncology. Regulatory advice should be sought very early in the design and preparation of clinical trials of innovative medicines, for which regulatory approval may ultimately be sought. Aligning strategic, scientific, regulatory, health technology and funding requirements from the inception of a clinical trial is especially important as these are very expensive therapies. The model for drug development for cell therapy in paediatric oncology could also involve a 'later stage handoff' to industry after early development in academic hands. Finally, and very importantly, strategies must evolve to ensure appropriate ease of access for children who need and could potentially benefit from these therapies. Highlights: Chimeric antigen receptor T-cell therapy has substantial promise for children and adolescents with cancer. However, there are biological, clinical and manufacturing challenges. Strategies must evolve to ensure appropriate access to these novel treatments. Comparative benefits of chimeric antigen receptor T-cells and all adoptive cell therapies need evaluation. Strategic, scientific, regulatory, health technology assessment and funding requirements should be aligned.